Update on Pulmonary Toxicity Induced by New Breast Cancer Treatments - Belluzzi L; Martinelli G; Medici B; Farina A; Martinelli E; Canino F; Caggia F; Molinaro A; Barbolini M; Tamburrano F; Moscetti L; Piacentini F; et al. (Breast Cancer: Targets and Therapy)
Lorenzo Belluzzi,1,2,* Giulio Martinelli,1,2,* Bianca Medici,1,2 Alessandro Farina,1 Enrica Martinelli,1 Fabio Canino,1,2 Federica Caggia,2,3 Alessia Molinaro,1 Monica Barbolini,2,4 Fabio Tamburrano,1 Luca Moscetti,2,4 Federico Piacentini,1,2 Massimo Dominici,1 Claudia Omarini2,4 1Department of Medical and Surgical Sciences for Children & Adults, University Hospital of Modena, Modena, Italy; 2GOIRC (Gruppo Oncologico Italiano di Ricerca Clinica), Parma, Italy; 3Department of Training, Research and Innovation, University Hospital of Modena, Modena, Italy; 4Department of Medical Oncology, University Hospital of Modena, Modena, Italy*These authors contributed equally to this workCorrespondence: Claudia Omarini, Division of Medical Oncology, University Hospital of Modena, Via del Pozzo 71, 41122, Modena, Italy, Tel +39 059 4222845, Email claudia.omarini@gmail.comAbstract: In recent years, new anticancer drugs have been investigated and approved for the treatment of breast cancer based on improved survival outcomes. However, these new treatments have specific class-related side effects. Pulmonary toxicity has been identified as an adverse event of special interest with everolimus, and is becoming an increasingly significant clinical challenge with the recent approval of trastuzumab deruxtecan. Overall, the risk of pulmonary toxicity is quite low but in some cases lung damage can be fatal. We conducted an update including the available published data regarding the incidence, mechanisms of pathogenesis, clinical presentations, and treatment of lung toxicity induced by new anticancer drugs. A literature search was performed between January and June 2024, considering papers, clinical trials, case reports, case series, meta-analyses, and systematic reviews published from January 2014 to June 2024. We also provide an algorithm for diagnosis and treatment, along with real-life cases managed at the Modena Cancer Center. Data provided here show that pulmonary toxicity is a quite frequent side effect and underline that early recognition and prompt treatment are crucial for the best outcome of patients, whose overall prognosis is being improved by the availability of these new anticancer agents.Keywords: breast cancer, lung toxicity, Pulmonary toxicity, interstitial lung disease, pneumonia, trastuzumab deruxtecan, CDK4/6i